Performing history and cultural memory through ancient drama: the case of contemporary Polish theatre. (17th March 2023) - Budzowska, Małgorzata
Abstract: By the mode of representation of human life processes, theatre from its very beginning has contributed to maintaining or confronting a given social order, so as to complete its ethico-political function. One of the genuinely politically involved issues to discuss in theatre has become the past. However, on stage, history is recalled to serve both the present and the future in order to construct and develop cultural memory. Classical reception provides a comprehensive method of coping with the past, empowering the performance of the political. This article ponders the development of the ethico-political function of contemporary theatre in Poland by providing three case studies of productions that perform history and cultural memory in a specifically chosen location: Orestes by Michał Zadara, Ajax. The Machine by Natalia Korczakowska, and Wałęsa at Colonus by Bartosz Szydłowski. The conceptual framework of the analysis is constructed from the idea of the political, adapted to the specificity of the Romantic paradigm that furnishes the ground for the study of performing history and cultural memory in Polish theatre. The issue in focus is to observe how the classical reception of ancient dramas can be a performance of the political through an indirect recalling of the historical past.